ANTIOXIDANT AND ANTIGLYCATION POTENTIAL OF DEVELOPED POLYHERBAL FORMULATIONS AND EXTRACTED PHYTOCHEMICALS - Taj Muhammad; Zahida Parveen; Saira Farman; Beenish Khurshid; Muhammad Assad; Nosheen Faiz; Naeema Begum (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Diabetes mellitus is a chronic metabolic disorder characterized by insulin deficiency or its ineffectiveness though produced by the body. More than 90% of patients affected by diabetes are of type II. Advanced Glycated End products (AGEs) in correlation with oxidative stress are mainly responsible for the long-term complications of diabetes. The present study was designed to evaluate antioxidant and antiglycation properties of three individual plants including Trillidium goanum, Centorium tenuiflorum and Rubinia pseudoacacia as well as polyherbal formulations (n=11). Results of crude extracts revealed highest antioxidant and antiglycation activity of polyherbal formulation S22 (Centorium tenuiflorum+Morchella conica) with IC50 values of 21.63±0.15µg/mL and 10.63±1.72µg/mL respectively. When the data was compared for phytochemicals, it was noticed that phenols and tannins from S28 (Trillidium goanum+Centorium tenuiflorum+Morchella conica+Rubinia pseudoacacia) showed the potent antioxidant activity by showing IC50 values of 7.6±0.36µg/mL and 8.17± 1.69 µg/mL respectively. However, for antiglycation properties phenols and tannins for S28 and S29 were found to be potent. The IC50 values were 7.046±3.19µg/mL (phenols, S28), 7.33±2.2µg/mL (tannins, S28), 5.34±1.86µg/mL (Phenols, S29) and 58.07±1.59µg/mL (tannins, S29). Additionally, quantification data indicated highest concentrations of phenols, flavonoids, and tannins in polyherbal formulation S28 which gives an indication of highest antioxidant and antiglycation potential of formulation S28.